De la recherche scientifique au documentaire sur la migration, des mémoires en mouvement - Eva Léger (Cahiers de Civilisation Espagnole Contemporaine)
This introspective text proposes to explore the line of thought that brought me from scientific research to documentary writing. It exposes the subject of the audio documentary entitled “From Alicante to Tulle, a memory in exile” produced in 2018 in collaboration with Julien Varigault, to address more widely the question of memories of the Spanish exile and how they imposed themselves on me as reference framework in my own life course. By exploring this painful past, this article questions the mark and our possible traces on the present.